A national open‐access research registry to improve recruitment to clinical studies. Issue 1 (9th December 2021) - Kotting, Piers; Smith, Adam; O'Hare, Megan B.; Giebel, Clarissa; Mendis, Lakshini; Shaw, Clare; Shillito, Imogen; Rossor, Martin N.
Abstract: Introduction: Barriers to recruitment for dementia studies are well documented. As part of the UK government's Dementia 2020 strategy, a nationally consistent system to increase public engagement and participation in research was launched in February 2015. Methods: We describe the development of the "Join Dementia Research" registry, including evolution of policy, involvement of people with dementia in co‐production, data requirements, governance, technology, and the impact on study recruitment and what factors may have contributed to the services success. Results: The UK‐wide online, telephone, and postal service has registered 47, 071 volunteers, with 33, 139 people (67.9% of all volunteers) taking part in 378 studies, with 49, 954 total study enrolments. This has taken place across 295 research sites, involved 1522 researchers, and resulted in 134 peer‐reviewed publications. Discussion: Public registries of individuals interested in research, with user‐provided data enabling basic phenotyping, are effective at increasing public engagement with research and removing barriers to study recruitment. Deeper pheno/genotyping could be undertaken to improve matching, but how and when that information is collected will be a key factor.